Transposing Proper Names in Frank McCourt’s Memoir Angela’s Ashes from English into Maltese - Grima, Kenneth (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
This paper focuses on the transposition from English into Maltese of the various proper names encountered in Frank McCourt’s memoir Angela’s Ashes (Chapter 1). To achieve this aim, an extended practical translation exercise by the author himself is used. Eight different categories of proper names were identified in the source-text ranging from common people names to nicknames, titles and forms of address. Four different categories of cross-cultural transposition of proper names were considered, although only two were actually used. Various translation strategies were adopted ranging from non-translation to modification, depending on whether the particular proper name has a ‘conventional’ meaning or a culturally ‘loaded’ meaning. Although cultural losses were unavoidable, cultural gains were also experienced. Wherever possible, the original proper names were preserved to avoid any change in meaning and interference in their functionality as cultural markers. Moreover, a semantic creative translation was preferred, especially with proper names that were culturally and semantically loaded to reduce the amount of processing effort required by the target-reader and to minimize the cultural losses of relevant contextual and cultural implications in the target-text.